Differential expression of microRNAs in hematopoietic cell lineages - Merkerova, Michaela; Belickova, Monika; Bruchova, Hana (European journal of haematology, 2008)
OBJECTIVES: MicroRNAs (miRNAs) play key roles in a wide variety of normal and pathological cellular processes. A number of studies identified hematopoietic-specific miRNAs that are necessary for correct function of blood cells. Out of our microarray data, we chose 13 miRNAs that showed differential expression in peripheral blood cells (miR-15b, miR-16, miR-24, miR-30c, miR-106b, miR-142-3p, miR-142-5p, miR-150, miR-155, miR-181, miR-223, miR-342, and miR-451) and examined their expression in separated hematopoietic cell lineages. METHODS: Using quantitative real-time polymerase chain reaction, we measured relative expression of the miRNAs in fractions of reticulocytes, platelets, granulocytes, monocytes, B- and T-lymphocytes as well as in several hematopoietic cell lines. RESULTS: We observed that miR-16 and miR-142-3p were highly expressed in all native cell lineages, miR-451 reached the maximal expression in reticulocytes, miR-223 in platelets, granulocytes and monocytes, and miR-150 in B- and T-lymphocytes. Hierarchical clustering analysis grouped the lineage samples according to their origin based on the expression of these miRNAs. To validate discrimination power of the miRNAs, we quantified expression of the 13 miRNAs in several immortalized cell lines. Although the cell lines showed miRNA expression patterns considerably different from those of native cell lineages, clustering analysis distinguished between myeloid, lymphoid and non-hematopoietic cells. CONCLUSIONS: In conclusion, the study reports the expression levels of 13 miRNAs in particular blood cell lineages as well as immortalized cell lines. We demonstrate that the expression profiles of these miRNAs may be used for discrimination of the hematopoietic cell lineages.
Keywords: trombocyty; Reticulocytes; Gene Expression Profiling; Cell Differentiation; Leukocytes; K562 Cells; Lymphoid Progenitor Cells; mikro RNA; Gene Expression Regulation; HeLa Cells; prekurzorové buňky granulocytů; buňky K562; MicroRNAs; retikulocyty; regulace genové exprese; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Humans; Granulocyte Precursor Cells; stanovení celkové genové exprese; buněčná diferenciace; Oligonucleotide Array Sequence Analysis; Blood Platelets; leukocyty; lymfoidní progenitorové buňky; HeLa buňky; lidé